Fenomenalny strzelec. (Gdynia : [s.n.], 1946)
Afisz inf. o występach cyrkowych w Gdyni we wrześniu 1946 r.
Keywords: Cyrk -- Polska -- 1945-1970 -- druki ulotne; Gdynia (Polska) -- 1945-1970 -- druki ulotne; Gdynia (Polska) -- 1945-1970 -- źródła